Linking Financial Performance to Profit Growth: Empirical Insights from Pharmaceutical Firms in Indonesia - Dian Anggraeny Rahim; Irma Citarayani; Maevy Caroline Marbun (E-Jurnal Akuntansi, 2025)
Profit growth in pharmaceutical companies is regarded as a meaningful indicator of successful financial performance. However, achieving sustained profitability in this sector remains challenging due to structural vulnerabilities, including intense industry competition, a heavy reliance on imported raw materials, and persistent volatility in foreign exchange rates. These external pressures underscore the need for robust financial management strategies to ensure long-term viability. In response to these dynamics, this study investigates the determinants of profit growth among pharmaceutical firms listed on the Indonesia Stock Exchange (IDX) over the 2014–2024 period. Drawing on secondary data sourced from company financial statements, the analysis employs panel data regression to examine the influence of the cash ratio (CR), total asset turnover (TATO), and debt-to-asset ratio (DAR) on profit growth (PG). To complement the regression analysis, the study also applies the Simple Moving Average (SMA) method using a five-year rolling window to forecast future trends in the observed variables. The empirical findings reveal that both CR and TATO exert a positive and statistically significant influence on profit growth, highlighting the importance of liquidity and asset efficiency in enhancing firm profitability. Conversely, DAR does not exhibit a significant effect, suggesting that leverage plays a less critical role in shaping earnings performance within the context of the pharmaceutical industry during the observed period. Forecasting analysis supports these insights. All variables meet the criteria for model feasibility, with Mean Absolute Percentage Error (MAPE) values ranging between 20% and 50%, indicating moderate predictive accuracy. The projections show an upward trend in PG and TATO, while CR remains relatively stable and DAR demonstrates a gradual decline. These trends point to an industry trajectory characterized by improving operational performance, sustained liquidity, and cautious deleveraging. Overall, the results provide relevant empirical evidence on the financial performance drivers in Indonesia’s pharmaceutical sector. They also offer practical implications for corporate managers and stakeholders, emphasizing the strategic value of liquidity and asset utilization in fostering profit sustainability under volatile market conditions.Keywords: Pharmaceutical Companies; Financial Performance; Profit Growth; Forecasting